Evaluating the Impact of Faculty-Embedded Tutor Training Program Factors on Perceived Future Training Needs Using Structural Equation Modeling. (6th February 2012) - Calma, Angelito; Vista, Alvin
Abstract : This study examines participating tutors' four-year feedback on a faculty-embedded tutor training program using structural equation modeling. Data from 333 tutors across all four departments in the Faculty of Business and Economics was used. Results indicate that the quality of the training session directly influences tutors' perceived need for further skills development training and that the partial effect of facilitator effectiveness on the latter is not significant. This indicates that tutors' indication of their future need for relevant skills in teaching and use of technology is highly influenced by the quality of the training session and much less on the facilitator's effectiveness in delivering it. This has implications for both the way the tutor training program is perceived and the redevelopment of the questionnaire in the future.